THE PERFORMANCE LEVEL OF 10TH GRADE STUDENTS ENROLLED IN THE VOCATIONAL AND TECHNICAL TRACK (BTEC) IN THE READING AND WRITING SKILLS TEST IN THE DIRECTORATE OF EDUCATION FOR AL-JIZAH DISTRICT IN JORDAN - Oklah Mahmoud Al-Rashdan; Emad Suliman AL-Kaabneh; Maryam Suleiman Abu Gharah; Fayiz Mohammad AlKarazneh (International Journal of Teaching and Learning, 2025)
This study aimed to investigate the performance level of 10th-grade BTEC students in the reading and writing skills test administered in schools of the Ministry of Education in the Al-Jizah District. The study sample consisted of 143 male and female students from eight classes (BTEC 10th grade and academic 10th grade) across four schools in the Al-Jizah Directorate in Jordan. The study utilized a standardized test developed by the Jordanian Ministry of Education, assessing reading and writing skills in Arabic for the age group covering both BTEC and academic 10th-grade students. The test comprised ten items: seven multiple-choice questions and three essay-writing prompts. The results indicated statistically significant differences (α ≤ 0.05) attributable to gender, with an F-value of 18.795 and a significance level of 0.000, favoring female students. Additionally, statistically significant differences (α ≤ 0.05) were found based on the program type, with an F-value of 18.165 and a significance level of 0.000, favoring the academic program. However, no statistically significant differences (α ≤ 0.05) were observed due to the interaction between gender and program type, with an F-value of 2.582 and a significance level of 0.110. In light of these findings, the research recommends designing supportive educational programs to enhance male students' academic achievement by developing instructional strategies that address gender differences, thus improving their reading and writing skills. It also recommends enriching the BTEC program with additional reading and writing activities to ensure the development of students’ linguistic skills in line with contemporary demands, while fostering stimulating learning environments that consider individual differences.